Measuring the Impact of Computer Literacy Training Program on Alternative Learning Students in District of Tibiao - Salvacion, Christian Rae L.; Arevalo, Jan Cedric P.; Yumen, Nolan M. (Transpublika Publisher, 2024)
This study evaluates the effectiveness of a computer literacy training program for alternative learning students in Tibiao District, implemented from 2017 to 2023. The research employs a mixed-methods approach, combining quantitative surveys with qualitative open-ended questions, to assess the program's impact on participants' digital skills, daily application, and future opportunities. The study involved 100 alternative learning students, including out-of-school youth and adults from Tibiao and neighboring towns. Results indicate significant improvements across all skill areas, with the largest gains in word processing and email communication. Notably, 78% of participants rated the program highly, and 65% reported frequent application of new skills in daily life. The program demonstrated a transformative impact, with 85% of participants perceiving improved engagement in alternative learning and expanded opportunities. Age emerged as a significant predictor of skill improvement, with younger participants showing slightly higher gains. Qualitative analysis revealed themes of increased confidence, improved academic performance, and enhanced job prospects. The study also identified areas for improvement, including the need for targeted outreach to older learners and curriculum refinement based on initial skill levels. These findings contribute to the growing body of knowledge on digital literacy education in alternative learning contexts and provide valuable insights for policymakers and educators. The research underscores the critical role of computer literacy programs in bridging the digital divide and empowering non-traditional students in an increasingly technology-driven educational and professional landscape.